Detection of Epstein - Barr virus Capsid antigen (EBV CA) in Sera of Rheumatoid Arthritis, Reactive Arthritis and Ankylosing Spondylitis Patients - S. Jassim, Nuha; S. Aboud, Rana; T. Joda, Abbas; Y. Fadil, Hula; G. Al_Humadani, Faisal; M. Ahmed, Deena; A. Husaen, Maysooon (Iraqi Journal of Science, 2023)
To determine the role of Epstien barr virus (EBV) in the pathogenesis of Rheumatoid arthritis (RA) , Reactive arthritis (ReA) and Ankylosing spondylitis (AS) patients, sixty-two patients (52 patients with RA ,five patients with ReA and five patients with AS) have been investigated. The mean age (47.3, 47.7, 34.5) of RA, ReA , AS respectively and compared to 24 apparently healthy individuals with the mean age 28.3. All the study groups were carried out to measure antibodies of EBV (VCA) IgG and IgM by enzyme-linked immunosorbent assay (ELISA) technique. The result showed that there was a highly significant elevation ( p< 0.01) in the concentration of EBV (VCA) IgG Ab compared to control group, while there was no significant different (p> 0.05) in EBV (VCA) IgM Ab compared to control group. when the study groups were compared between each other in EBV (VCA) IgG Ab, the AS group had the higher mean of concentration 51.24 ± 2.19 U/ml while the RA mean concentration 40.82 ± 2.36 U/ml and finally ReA mean concentration was 38.24 ± 8.79 U/ml. compared to control group2.55 ± 0.03 U/ml . while comparison in mean level of EBV CA IgM Ab, the concentration was( 3.32 ± 0.40 , 5.24 ± 2.30 and 10.70 ± 6.89) U/ml for RA, ReA and AS reapectively compared to control group 0.122 ± 0.01 U/ml.The results of the present study indicate that infection with EBV play a role as a triggering factor in pathogensis of RA,Rea,AS.